Managing physiological disorders in arid fruits - Meena, R K; Sarolia, D K; Singh, R S; Bhargwa, R; Saroj, P L (Indian Horticulture, 2019)
Physiological disorders are mainly caused by changing environmental conditions such as temperature, moisture, unbalanced soil nutrients, inadequate or excess of certain soil minerals, extremes of soil pH and poor drainage. At present, the climatic scenario of arid region is also changing and the problems like frost, temperature and moisture fluctuation, high evaporation and low precipitation as well as nutrient imbalances are becoming a challenge for cultivation of many arid fruit crops. In this article we have discussed the problems associated with ber, pomegranate, aonla, date palm and bael especially physiological disorders which will certainly help the farmers in timely overcoming these maladies for getting satisfactory remunerative prices from arid fruit crops under hot ecosystem of western Rajasthan.